PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN - Vania Rosselivia; Sri Ekowati (Yayasan Insani Mandiri Santani, 2022)
This study aims to determine the effect of product quality and price on purchasing decisions on consumers at Amelia Bakery & Cake Bengkulu. This research uses quantitative descriptive research. The object of this research is the consumer of Amelia Bakery & Cake Bengkulu Store. Sampling using purposive sampling technique. The number of samples in this study were 130 respondents. Data collection methods used are observation, interviews and questionnaires or questionnaires. While the data analysis techniques using instrument tests, Respondents Response Analysis, Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination (R2) and also Test Hypothesis t and hypothesis F. The results of this study can be concluded that the Product Quality variable has a positive and significant effect on purchasing decisions at Amelia Bakery & Cake Bengkulu shop consumers, Price has a positive and significant impact on purchasing decisions at Amelia Bakery & Cake Bengkulu shop consumers, and Product Quality, and Prices together -the same has a positive and significant effect on purchasing decisions on consumers of Amelia Bakery & Cake Bengkulu stores. Keywords: Product Quality, price, purchasing decision.